2021
DOI: 10.1183/13993003.01459-2021
|View full text |Cite
|
Sign up to set email alerts
|

Lifting dyspnoea invisibility: COVID-19 face masks, the experience of breathing discomfort, and improved lung health perception – a French nationwide survey

Abstract: Question addressedIn contrast with pain, dyspnoea is not visible to the general public who lack the corresponding experiential baggage. We tested the hypotheses that the generalised use of face masks to fight SARS-CoV2 dissemination could change this and sensitise people to respiratory health.MethodsGeneral population polling (1012-person panel demographically representative of the adult French population –quota sampling method–; 517 women, 51%). 860 (85%) answered “no” to “treated for a chronic respiratory di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Thirdly, the ‘experiential understanding’ variable (experimental dyspnea-related improvement in understanding dyspneic patients’ experience) was the only variable that remained significantly associated with the overall course rating in multivariate analysis. The apparent importance of ‘experiential understanding’ in changing the participants’ perspective is consistent with observations showing that breathing discomfort linked to the use of COVID-19 face masks relates to improved perception of the lived experience of patients with chronic respiratory disease [ 20 ].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Thirdly, the ‘experiential understanding’ variable (experimental dyspnea-related improvement in understanding dyspneic patients’ experience) was the only variable that remained significantly associated with the overall course rating in multivariate analysis. The apparent importance of ‘experiential understanding’ in changing the participants’ perspective is consistent with observations showing that breathing discomfort linked to the use of COVID-19 face masks relates to improved perception of the lived experience of patients with chronic respiratory disease [ 20 ].…”
Section: Discussionsupporting
confidence: 74%
“…Ratings were particularly high, notably regarding dyspnea unpleasantness (median of 8). This observation is reminiscent of the high ratings associated, in the general public, with COVID-19 face mask-induced breathing discomfort, previously interpreted as illustrating the impossibility of imagining the intensity of a characteristic of which an individual has no direct experience [ 20 ]. We did not find differences according to the method used to self-induce dyspnea, in contrast with literature data differentiating inspiratory threshold loading and CO 2 stimulation [ 33 ].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Especially those with more significant health risks showed higher compliance levels to social distancing measures. 14 However, other studies found that vaccinated people increased their social contacts after vaccination and decreased other measures like mask wearing and careful hand washing. 22 , 23 Consequently, a preprint from Denmark found an increase in infections of 40% in the first 2 weeks after vaccination with Pfizer-BioNTech.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, wearing medical masks can provoke adverse health effects. Besides feeling discomfort [ 5 ], mask wearers report headaches [ 6 , 7 ], breathing difficulties [ 8 ], and can experience dermatological problems [ 9 ]. The irritation of nerves and other soft tissue in the neck and head region caused by the medical mask straps also contributes to headaches [ 6 ].…”
Section: Introductionmentioning
confidence: 99%